An NH2-MIL-125 (Ti)/Pt/g-C3N4 catalyst promoting visible-light photocatalytic H2 production. Issue 5 (29th March 2019) - Su, Zhuizhui; Zhang, Bingxing; Shi, Jinbiao; Tan, Dongxing; Zhang, Fanyu; Liu, Lifei; Tan, Xiuniang; Shao, Dan; Yang, Guanying; Zhang, Jianling
Abstract : In this study, we synthesized an efficient catalyst of NH2 -MIL-125 (Ti)/Pt/g-C3 N4 composites for the visible-light-driven H2 production reaction. Abstract : In this study, we synthesized an efficient catalyst of NH2 -MIL-125 (Ti)/Pt/g-C3 N4 composites for the visible-light-driven H2 production reaction. Compared with Pt/g-C3 N4, the as-synthesized NH2 -MIL-125 (Ti)/Pt/g-C3 N4 composites show greatly improved performance for photocatalytic H2 production. The highest H2 production rate of the NH2 -MIL-125 (Ti)/Pt/g-C3 N4 catalyst was found to be 3986 μmol h −1 g −1, which is much higher than that of Pt/g-C3 N4 (1100 μmol h −1 g −1 ) under the same experimental conditions. The NH2 -MIL-125 (Ti)/Pt/g-C3 N4 catalyst has application potential for other photocatalytic reactions.